Tingkat kesukaan lebah madu Apis Mellifera L. terhadap pakan tambahan campuran madu mengkudu - Budiaman Budiaman; B. Putranto (Perhimpunan Entomologi Indonesia, 2007)
Feeding supplementary food containing nony fruit juice was tested on honeybee colonies in honey producing . The aims of this research were (1) to determine the preference level of honeybees to the supplementary food containing honey and nony mixture, (2) to identify the organoleptic properties of the produced honeyessence of nony, (3) to determine fiber content of produced honey-essence of nony, and (4) to identify the colours of honey produced. The design used in the experiment was Latin Square Design. There were four treatments namely each concentration : A (0%) as control, B (12,5%), C (25%) dan D (37,5%) in dilution of supplementary food an amount of 600 grams wich consist of nony fruit juice and water. Each composition of dilution were A (300, 0, 300), B (225, 75, 300), C (150, 150, 300) dan D (75, 225, 300) . Every one replication was done for six days with six day interval. The result were as follows: The higher concentration of nony juice in the food suplement the smaller food were taken. The differences in the olour, the flavour and the taste of the artificial honey didn’ depend on the amount of the food suplement taken honey bees, but depend on nony fruits juice concentration in the honey produced. The higher concentration of nony fruit juice in the artificial honey produced the darken in colour, sour in taste and the weaken in flavour. Feeding with food suplement containing nony juice increases the fiber content in the honey.